Toxicity of 13 different antibiotics towards freshwater green algae Pseudokirchneriella subcapitata and their modes of action. (February 2017) - Fu, Ling; Huang, Tao; Wang, Shuo; Wang, Xiaohong; Su, Limin; Li, Chao; Zhao, Yuanhui
Abstract: Although modes of action (MOAs) play a key role in the understanding of the toxic mechanism of chemicals, the MOAs have not been investigated for antibiotics to green algae. This paper is to discriminate excess toxicity from baseline level and investigate the MOAs of 13 different antibiotics to algae by using the determined toxicity values. Comparison of the toxicities shows that the inhibitors of protein synthesis to bacteria, such as azithromycin, doxycycline, florfenicol and oxytetracycline, exhibit significantly toxic effects to algae. On the other hand, the cell wall synthesis inhibitors, such as cefotaxime and amoxicillin, show relatively low toxic effects to the algae. The concentrations determined by HPLC indicate that quinocetone and amoxicillin can be easily photodegraded or hydrolyzed during the toxic tests. The toxic effects of quinocetone and amoxicillin to the algae are attributed to not only their parent compounds, but also their metabolites. Investigation on the mode of action shows that, except rifampicin, all the tested antibiotics exhibit excess toxicity to Pseudokirchneriella subcapitata ( P. subcapitata) . These antibiotics can be identified as reactive modes of action to the algae. They act as electrophilic mechanism of action to P. subcapitata . These results are valuable for the understanding of the toxic mechanism to algae. Highlights: Great correlations were observed between toxicities of different exposure periods. Inhibitors of protein synthesis to bacteria exhibit greatly toxic effects to algae. Antibiotics exhibit excess toxicity and can be identified as reactive MOA to algae. Antibiotics act as electrophilic mechanism of action to P. subcapitata.